Kinder und ihr Geschlecht - Rendtorff, Barbara; Prengel, Annedore (Jahrbuch Frauen- und Geschlechterforschung in der Erziehungswissenschaft, 2008)
The connection between child development and gender can only be traced by analysing the complex interplay of many different individual and social, political and social, historical and cultural factors - it cannot be explored or empirically measured with the help of selective research. The current yearbook therefore presents theoretical, empirical-qualitative and empirically quantitative contributions and research reports that examine gender aspects of childhood life and learning.